Design and development of vanadium redox flow battery (V-RFB) cell stack - Nurizzati, Md Nizam; M. H., Zulkhifli; A. C., Khor; Mohd Rusllim, Mohamed; M. H., Sulaiman (IEEE, 2016)
The purpose of this paper is to demonstrate the summarization of work on experimental characterisation of vanadium redox flow battery (V-RFB). The aim of the study is to design a functional prototype of V-RFB and investigate the performance of characterisation of V-RFB at specific current density. Experiment was carried on 110.25cm 2 prototype of unit cell. The results from the performance test of the developed V-RFB including few obstacles faced have been presented and analysed. Further works is discussed.